Assimilatory potential of helicoverpa armigera reared on host (chickpea) and nonhost (cassia tora) diets - Dawkar, Vishal V.; Chikate, Yojana R.; Gupta, Vidya S.; Slade, Susan E.; Giri, Ashok P. (Journal of Proteome Research, 2011)
Adaptation to plant allelochemicals is a crucial aspect of herbivore chemical ecology. To understand an insect ecology, we studied an effect of nonhost Cassia tora seed-based diet (Ct) on growth, development, and molecular responses in Helicoverpa armigera. We employed a comparative approach to investigate the proteomic differences in gut, hemolymph, and frass of H. armigera reared on a normal (chickpea seed-based, Cp) and Ct diet. In this study, a total of 46 proteins were identified by nano-LC-MS(E). Among them, 17 proteins were up-regulated and 29 proteins were down-regulated when larvae were exposed to the Ct diet. Database searches combined with GO analysis revealed that gut proteases engrossed in digestion, proteins crucial for immunity, adaptive responses to stress, and detoxification were down-regulated in the Ct fed larvae. Proteins identified in H. armigera hemolymph were found to be involved in defense mechanisms. Moreover, proteins found in frass of the Ct fed larvae were observed to participate in energy metabolism. Biochemical and quantitative real-time PCR analysis of selected candidate proteins showed differential gene expression patterns and corroborated with the proteomic data. Our results suggest that the Ct diet could alter expression of proteins related to digestion, absorption of nutrients, adaptation, defense mechanisms, and energy metabolism in H. armigera.
Keywords: adaptation; Cassia tora; Gene expression; Helicoverpa armigera; proteomics

Molecular insights into resistance mechanisms of lepidopteran insect pests against toxicants - Dawkar, Vishal V.; Chikate, Yojana R.; Lomate, Purushottam R.; Dholakia, Bhushan B.; Gupta, Vidya S.; Giri, Ashok P. (Journal of Proteome Research, 2013)
Insect pests remain a major reason for crop loss worldwide despite extensive use of chemical insecticides. More than B 50% of all insecticides are organophosphates, followed by synthetic pyrethroids, organochlorines, carbamates, and biopesticides, and their continued use may have many environmental, agricultural, medical, and socioeconomic issues. Importantly, only a countable number of insects have acquired the status of crop pests, mostly due to monoculture of crop plants and polyphagous nature of the insects. We focus on A adaptations of Lepidopteran insects to phytochemicals and synthetic pesticides in native and modern agricultural systems. Because of heavy use of chemical insecticides, a strong selection pressure is imposed on insect populations, resulting in the emergence of resistance against candidate compound(s). Current knowledge suggests that insects generally implement a three-tier system to overcome the effect of toxic compounds at physiological, biochemical, and genetic levels. Furthermore, we have discussed whether the adaptation to phytochemicals provides an advantage to the insect while encountering synthetic insecticide molecules. Specific metabolic pathways employed by insects to convert deterrents into less toxic forms or their removal from the system are highlighted. Using the proteomics approach, insect proteins interacting with insecticides can be identified, and their modification in resistant insects can be characterized. Also, systems biology studies can offer useful cues to decipher the molecular networks participating in the metabolism of detrimental compounds.
Keywords: field crops; insect-pests; insecticide; Lepidoptera; proteomics; resistance mechanisms

Proteomic study reveals downregulation of apolipoprotein A1 in plasma of poorly controlled diabetes: a pilot study - Bhonsle, Hemangi S.; Korwar, Arvind M.; Chougale, Ashok D.; Kote, Sachin S.; Dhande, Nitin L.; Shelgikar, Kishore M.; Kulkarni, Mahesh J. (Molecular Medicine Reports, 2013)
Proteomic approaches aid in gaining a better understanding of the pathophysiology of diabetic complications. In view of this, differential protein expression in diabetic plasma samples was studied by a combination of proteomic and western blot analyses. Diabetic plasma samples were categorized based on glycated haemoglobin levels as controlled diabetes (CD; 7-8%), poorly controlled diabetes (PCD; >8%) and non-diabetic control (ND;<6.4%). Two-dimensional electrophoresis and liquid chromatography-mass spectrometry revealed differential expression of proteins including upregulation of fibrinogen and haptoglobin and downregulation of vitamin D binding protein, alpha-1-antitrypsin, transthyretin and apolipoprotein A1 (Apo A1) in diabetic compared with non-diabetic plasma samples. Amongst these proteins, Apo A1 downregulation was prominent in PCD. Downregulation of Apo A1 may serve as an early predictive marker of diabetic complications.
Keywords: biomarker; HbA1c; proteomics

Proteomics of arsenic stress in the gram-positive organism Exiguobacterium sp PS NCIM 5463 - Sacheti, Poonam; Patil, Rajendra; Dube, Ankita; Bhonsle, Hemangi S.; Thombre, Dipalee; Marathe, Sayali; Vidhate, Ravindra; Wagh, Priyanka; Kulkarni, Mahesh J.; Rapole, Srikanth; Gade, Wasudeo N. (Applied Microbiology and Biotechnology, 2014)
The general responses of microorganisms to environmental onslaughts are modulated by altering the gene expression pattern to reduce damage in the cell and produce compensating stress responses. The present study attempts to unravel the response of the Gram-positive Exiguobacterium sp. PS NCIM 5463 in the presence of [As(III)] and arsenate [As(V)] using comparative proteomics via two-dimension gel electrophoresis (2-DE) coupled with identification of proteins using matrix-assisted laser desorption/ionisation (MALDI-TOF/MALDI-TOF/TOF). Out of 926 Coomassie-stained proteins, 45 were differentially expressed (p < 0.05). Considering the resolution and abundance level, 24 spots (peptides) were subjected to MALDI analysis, identified and categorised into several functional categories, viz., nitrogen metabolism, energy and stress regulators, carbohydrate metabolism, protein synthesis components and others. A functional role of each protein is discussed in Exiguobacterium sp. PS 5463 under arsenic stress and validated at their transcript level using a quantitative real-time polymerase chain reaction. Unlike previous reports that unravel the responses toward arsenic stress in Gram-negative organisms, the present study identified new proteins under arsenic stress in a Gram-positive organism, Exiguobacterium sp. PS NCIM 5463, which could elucidate the physiology of organisms under arsenic stress.
Keywords: Arsenic; Exiguobacterium; proteomics; Stress; Transcriptomics

Qualitative and quantitative proteomic analysis of vitamin C induced changes in mycobacterium smegmatis - Mishra, Abhishek; Sarkar, Dhiman (Frontiers in Microbiology, 2015)
Vitamin C is a critical dietary nutrient in human which has a wide range of regulatory effects on gene expression and physiology of Mycobacterium tuberculosis that leads to a dormant drug-tolerant phenotype. In the presence of iron, vitamin C shows a high bactericidal activity even in the drug resistant phenotype of M. tuberculosis. The regulatory mechanisms underlying vitamin C induced adaptations are largely unknown due to lack of functional genomics data in this field. In this study, we attempt to characterize the direct effect of vitamin C treatment on the physiology of actively growing Mycobacterium smegmatis. The study chose M. smegmatis as it is a fast-growing bacterium and a non-pathogenic model system which shares many physiological features with the pathogenic M. tuberculosis including dormancy and its regulation. The proteomic adaptation of M. smegmatis on vitamin C treatment demonstrates the important changes in cellular and metabolic process such as reversal of tricarboxylic acid cycle, decrease in ATP synthesis, decrease in iron acquisition and storage, and induction of dormancy regulators WhiB3, PhoP, and Lsr2.
Keywords: dormancy; Mycobacterium smegmatis; proteomics; tuberculosis; vitamin C

Expression of proteins involved in digestion and detoxification are regulated in helicoverpa armigera to cope up with chlorpyrifos insecticide - Dawkar, Vishal V.; Chikate, Yojana R.; More, Tushar H.; Gupta, Vidya S.; Giri, Ashok P. (Insect Science, 2016)
Helicoverpa armigera is a key pest in many vital crops, which is mainly controlled by chemical strategies. To manage this pest is becoming challenging due to its ability and evolution of resistance against insecticides. Further, its subsequent spread on nonhost plant is remarkable in recent times. Hence, decoding resistance mechanism against phytochemicals and synthetic insecticides is a major challenge. The present work describes that the digestion, defense and immunity related enzymes are associated with chlorpyrifos resistance in H. armigera. Proteomic analysis of H. armigera gut tissue upon feeding on chlorpyrifos containing diet (CH) and artificial diet (AD) using nano-liquid chromatography-mass spectrometry identified upregulated 23-proteins in CH fed larvae. Database searches combined with gene ontology analysis revealed that the identified gut proteins engrossed in digestion, proteins crucial for immunity, adaptive responses to stress, and detoxification. Biochemical and quantitative real-time polymerase chain reaction analysis of candidate proteins indicated that insects were struggling to get nutrients and energy in presence of CH, while at the same time endeavoring to metabolize chlorpyrifos. Moreover, we proposed a potential processing pathway of chlorpyrifos in H. armigera gut by examining the metabolites using gas chromatography-mass spectrometry. H. armigera exhibit a range of intriguing behavioral, morphological adaptations and resistance to insecticides by regulating expression of proteins involved in digestion and detoxification mechanisms to cope up with chlorpyrifos. In these contexts, as gut is a rich repository of biological information; profound analysis of gut tissues can give clues of detoxification and resistance mechanism in insects.
Keywords: chlorpyrifos; Helicoverpa armigera; insecticide resistance; proteomics; real-time PCR

Fusarium oxysporum mediates systems metabolic reprogramming of chickpea roots as revealed by a combination of proteomics and metabolomics - Kumar, Yashwant; Zhang, Limin; Panigrahi, Priyabrata; Dholakia, Bhushan B.; Dewangan, Veena; Chavan, Sachin G.; Kunjir, Shrikant M.; Wu, Xiangyu; Li, Ning; Rajmohanan, Pattuparambil R.; Kadoo, Narendra Y.; Giri, Ashok P.; et al. (Plant Biotechnology Journal, 2016)
Molecular changes elicited by plants in response to fungal attack and how this affects plant-pathogen interaction, including susceptibility or resistance, remain elusive. We studied the dynamics in root metabolism during compatible and incompatible interactions between chickpea and Fusarium oxysporum f. sp. ciceri (Foc), using quantitative label-free proteomics and NMR-based metabolomics. Results demonstrated differential expression of proteins and metabolites upon Foc inoculations in the resistant plants compared with the susceptible ones. Additionally, expression analysis of candidate genes supported the proteomic and metabolic variations in the chickpea roots upon Foc inoculation. In particular, we found that the resistant plants revealed significant increase in the carbon and nitrogen metabolism; generation of reactive oxygen species (ROS), lignification and phytoalexins. The levels of some of the pathogenesis-related proteins were significantly higher upon Foc inoculation in the resistant plant. Interestingly, results also exhibited the crucial role of altered Yang cycle, which contributed in different methylation reactions and unfolded protein response in the chickpea roots against Foc. Overall, the observed modulations in the metabolic flux as outcome of several orchestrated molecular events are determinant of plant's role in chickpea-Foc interactions.
Keywords: Chickpea; fusarium oxysporum; Metabolomics; NMR; plant-pathogen interaction; proteomics

Nutritional quality and antioxidant activity of wheatgrass (Triticum aestivum) unwrap by proteome profiling and DPPH and FRAP assays - Parit, Santosh B.; Dawkar, Vishal V.; Tanpure, Rahul S.; Pai, Sandeep R.; Chougale, Ashok D. (Journal of Food Science, 2018)
Precious contribution of plants in the field of medicine is very well known. Wheat (Triticum aestivum) seeds and seedlings are an important source of food and feed due to the presence of various health-promoting compounds. Proteomic analysis of three seed developmental stages (0, 8, and 16 days after germination [DAG]) of wheat was carried out using liquid chromatography-mass spectrometry. A total of 297 proteins were identified and their functional annotation revealed that a majority of them were involved in preventing many diseases, oxidative stress, primary metabolism, storage, and energy related mechanisms. Particularly to mention, peroxidases, superoxide dismutases, and cytochromes are abundantly present in wheatgrass. In the ferric-reducing antioxidant power assay, antioxidant activity was increased by 1.55 times after 16 DAG as compared to 0 DAG, however it was decreased after 8 DAG. The antioxidant activity of the plant extracts by DPPH had an increasing trend after all the three time points. The percent radical scavenging activity of extract by DPPH was 15, 22, and 30 after 0, 8, and 16 DAG, respectively. Observations obtained revealed that antioxidant power of the plants is directly proportional to the age of seedlings. Data attained on wheatgrass showing that it can be a strong antioxidant agent due to its free radical scavenging activity and could be used in stress and nourishing human health. Practical ApplicationWheatgrass contains minerals, phytochemicals, active enzymes, and vitamins that can be easily absorbed. The consumption of wheatgrass juice can give better health benefits. Information about beneficial properties of wheat grass juice is clearly mentioned in this work.Proteins found in wheatgrass are known to be involved in preventing many diseases, oxidative stress, primary metabolism, storage, and energy-related mechanisms. Results of this work revealed that Triticum aestivum seedlings can act as an antioxidant agent due to their free radical scavenging activity and can be constructive to control or treat many health complications. From all these results we believed that wheatgrass can be used for the nourishment of humans.
Keywords: Antioxidant; LC-MSE; peroxidase; proteomics; Triticum aestivum; wheatgrass

Flower bud proteome reveals modulation of sex-biased proteins potentially associated with sex expression and modification in dioecious Coccinia grandis - Devani, Ravi Suresh; Chirmade, Tejas; Sinha, Sangram; Bendahmane, Abdelhafid; Dholakia, Bhushan B.; Banerjee, Anjan Kumar; Banerjee, Jayeeta (BMC Plant Biology, 2019)
BackgroundDioecy is an important sexual system wherein, male and female flowers are borne on separate unisexual plants. Knowledge of sex-related differences can enhance our understanding in molecular and developmental processes leading to unisexual flower development. Coccinia grandis is a dioecious species belonging to Cucurbitaceae, a family well-known for diverse sexual forms. Male and female plants have 22A+XY and 22A+XX chromosomes, respectively. Previously, we have reported a gynomonoecious form (22A+XX) of C. grandis bearing morphologically hermaphrodite flowers (GyM-H) and female flowers (GyM-F). Also, we have showed that foliar spray of AgNO3 on female plant induces morphologically hermaphrodite bud development (Ag-H) despite the absence of Y-chromosome.ResultsTo identify sex-related differences, total proteomes from male, female, GyM-H and Ag-H flower buds at early and middle stages of development were analysed by label-free proteomics. Protein search against the cucumber protein sequences (Phytozome) as well as in silico translated C. grandis flower bud transcriptome database, resulted in the identification of 2426 and 3385 proteins (FDR <= 1%), respectively. The latter database was chosen for further analysis as it led to the detection of higher number of proteins. Identified proteins were annotated using BLAST2GO pipeline. SWATH-MS-based comparative abundance analysis between Female_Early_vs_Male_Early, Ag_Early_vs_Female_Early, GyM-H_Middle_vs_Male_Middle and Ag_Middle_vs_ Male_Middle led to the identification of 650, 1108, 905 and 805 differentially expressed proteins, respectively, at fold change >= 1.5 and P <= 0.05. Ethylene biosynthesis-related candidates as highlighted in protein interaction network were upregulated in female buds compared to male buds. AgNO3 treatment on female plant induced proteins related to pollen development in Ag-H buds. Additionally, a few proteins governing pollen germination and tube growth were highly enriched in male buds compared to Ag-H and GyM-H buds.ConclusionOverall, current proteomic analysis provides insights in the identification of key proteins governing dioecy and unisexual flower development in cucurbitaceae, the second largest horticultural family in terms of economic importance. Also, our results suggest that the ethylene-mediated stamen inhibition might be conserved in dioecious C. grandis similar to its monoecious cucurbit relatives. Further, male-biased proteins associated with pollen germination and tube growth identified here can help in understanding pollen fertility.
Keywords: Coccinia grandis; Dioecy; Pollen fertility; proteomics; Sex modification; Stamen arrest

Oxidative stress induced by piperine leads to apoptosis in Candida albicans - Thakre, Archana; Jadhav, Vyankatesh; Kazi, Rubina; Shelar, Amruta; Patil, Rajendra; Kharat, Kiran; Zore, Gajanan; Karuppayil, S. Mohan (Medical Mycology, 2021)
Candida albicans is a member of pathogens with potential drug resistance threat that needs novel chemotherapeutic strategies. Considering the multifarious biological activities including bioenhancer activity, anti-Candida potential of piperine was evaluated against planktonic/biofilm and hyphal growth of C. albicans alone or in combination as a synergistic agent with fluconazole. Piperine inhibits planktonic growth at or less than 15 mu g/ml, hyphae induction at 5 mu g/ml concentration, and exhibits stage-dependent activity against biofilm growth of a fluconazole-resistant strain of C. albicans (ATCC10231). Though piperine couldn't kill inoculum completely at minimum inhibitory concentration (MIC), it is fungicidal at higher concentrations, as shown in apoptosis assay. FIC index values indicate that piperine exhibits excellent synergistic activity with fluconazole against planktonic (0.123) and biofilm (0.215) growth of an FLC resistant strain. Mode of anti-Candida activity was studied by identifying piperine responsive proteins wherein the abundance of 25 proteins involved in stress response, signal transduction and cell cycle were modulated (22 up and 3 downregulated) significantly in response to piperine (MIC50). Modulation of the proteins involved suggests that piperine affectsmembrane integrity leading to oxidative stress followed by cell cycle arrest and apoptosis in C. albicans. Flow cytometry-basedmitochondrialmembrane potential (MMP), cell cycle and apoptosis assay, as well as real-time quantitative polymerase chain reaction analysis of selected genes, confirms piperine induced oxidative stress (TRR1), cell cycle arrest and apoptosis (CaMCA1). Based on our results, we conclude that piperine inhibits planktonic and difficult-to treat-biofilm growth of C. albicans by affecting membrane integrity thereby inducing oxidative stress and apoptosis. Lay Abstract Piperine inhibit Candida albicans growth (planktonic and biofilm) significantly in our study. Piperine exhibits excellent synergistic potential with fluconazole The proteome analysis suggests that piperine induced membrane damage leads to oxidative stress followed by cell cycle arrest and apoptosis.
Keywords: Apoptosis; C. albicans; drug resistance; piperine; proteomics; synergy

Plasma-derived extracellular vesicles reveal galectin-3 binding protein as potential biomarker for early detection of glioma - Rana, Rashmi; Chauhan, Kirti; Gautam, Poonam; Kulkarni, Mahesh; Banarjee, Reema; Chugh, Parul; Chhabra, Satnam Singh; Acharya, Rajesh; Kalra, Samir Kumar; Gupta, Anshul; Jain, Sunila; Ganguly, Nirmal Kumar (Frontiers in Oncology, 2021)
{Gliomas are the most common type of the malignant brain tumor, which arise from glial cells. They make up about 40% of all primary brain tumors and around 70% of all primary malignant brain tumors. They can occur anywhere in the central nervous system (CNS) and have a poor prognosis. The average survival of glioma patients is approximately 6-15 months with poor aspects of life. In this edge, identification of proteins secreted by cancer cells is of special interest because it may provide a better understanding of tumor progression and provide early diagnosis of the diseases. Extracellular vesicles (EVs) were isolated from pooled plasma of healthy controls (n=03) and patients with different grades of glioma (Grade I or II or III
Keywords: blood-based biomarker; early detection; galectin-3 binding protein; plasma-derived extracellular vesicles; proteomics

Proteomic profile of candida albicans biofilm - Abdulghani, Mazen; Iram, Rasiqua; Chidrawar, Priti; Bhosle, Kajal; Kazi, Rubina; Patil, Rajendra; Kharat, Kiran; Zore, Gajanan (Journal of Proteomics, 2022)
Candida albicans biofilms are characterized by structural and cellular heterogeneity that confers antifungal resistance and immune evasion. Despite this, biofilm formation remains poorly understood. In this study, we used proteomic analysis to understand biofilm formation in C. albicans related to morphophysiological and architectural features. LC-MS/MS analysis revealed that 64 proteins were significantly modulated, of which 31 were upregulated and 33 were downregulated. The results indicate that metabolism (25 proteins), gene expression (13 proteins), stress response (7 proteins), and cell wall (5 proteins) composition are modulated. The rate of oxidative phosphorylation (OxPhos) and biosynthesis of UDP-N-acetylglucosamine, vitamin B6, and thiamine increased, while the rate of methionine biosynthesis decreased. There was a significant modification of the cell wall architecture due to higher levels of Sun41, Pir1 and Csh1 and increased glycosylation of proteins. It was observed that C. albicans induces hyphal growth by upregulating the expression of genes involved in cAMP-PKA and MAPK pathways. This study is significant in that it suggests an increase in OxPhos and alteration of cell wall architecture that could be contributing to the recalcitrance of C. albicans cells growing in biofilms. Nevertheless, a deeper investigation is needed to explore it further.Significance: Candida sps is included in the list of pathogens with potential drug resistance threat due to the increased frequency especially colonization of medical devices, and tissues among the patients, in recent years. Significance of our study is that we are reporting traits like modulation in cell wall composition, amino acid and vitamin biosynthesis and importantly energy generation (OxPhos) etc. These traits could be conferring antifungal resistance, host immune evasion etc. and thus survival, in addition to facilitating biofilm formation. These findings are expected to prime the further studies on devising potent strategy against biofilm growth among the patients.
Keywords: Biofilm; Candida albicans; Cell wall; LC-MS; Metabolism; MS; proteomics